Neo-right ‘witch hunt’: the rejection of democracy and social policies - Passos, Talita Kelly; Teixeira, Solange Maria (Argumentum, 2023)
This article analyses the performance of the New Right across the world and in Brazil, including its form and principals of action, evidence of the consequences for society, and a review of critical Literature. The staunch neo-right attack on democracy and social policies is highlighted, as well as the redefinition of historically constructed elements that contribute to the maintenance of life in society, and which aim to legitimise and intensify capitalist accumulation in its most destructive stage. It concludes that, for human survival there is an urgent need for a profound transformation and the dismantling of the capitalist rationality. Making readjustments or negotiations, as the Left has been doing in recent years, only feeds back the capitalist system, which reappears with greater, more devastating power. Keywords: New Right. Democracy. Social politics.